Investigation of an Atmospheric Pressure Plasma device for reduction of water use in sustainable cleaning of concentrating solar power mirrors - Gobey, Katherine (Cranfield University, 2023)
Concentrating Solar Power (CSP) is a method of renewable electricity generation that uses large areas of mirrors, that reflect and focus the sun’s energy onto a receiver which is then used to heat water to power a conventional steam turbine, generating electricity. These plants are typically located in areas with consistently high levels of sunlight which are typically arid desert areas where sand and dust is deposited onto the mirrors, reducing their reflectivity and thus the plant’s output. Conventional mirror washing consumes huge quantities of water, which is costly and incurs ethical and environmental concerns in areas already experiencing water scarcity. This work investigates the use of an atmospheric pressure plasma to induce a super-hydrophilic surface on the soiled mirrors which are then able to be cleaned with significantly lower quantities of water. Characterisation of the plasma torch is conducted, and surface energy modification effects investigated with regards to water spreading, evaporation, and travel. For cleaning trials, solar type mirrors were artificially soiled with sand gathered from a CSP plant, then plasma processed before being conventionally washed with water. Mirrors that were subject to soiling were successfully washed, as determined by reflectance measurements, with up to 87.5% less water than mirrors exposed to the same artificial soiling procedure but without plasma processing prior to washing. Plasma processed samples also exhibited self-cleaning properties when subject to condensation trials, mimicking overnight dew formation. There was no observed effect in either reduction or exacerbation of subsequent resoiling of plasma processed samples. Fundamental processes behind these effects are discussed and the application and implication of the work are considered.
Sansom, Chris - Associate Supervisor
Keywords: Plasma processing; surface energy modification; hydrophilic; nitrogen plasma; dielectric barrier discharge; heliostats; mirror soiling; renewable energy; solar thermal; anti soiling; self cleaning